Academics and their Respective Institution Practices of Continuous Professional Development : A case of Hawassa University, Ethiopia - Adane, medhanit; Asegedom, Amare; Weldemariyam, Kassahun (Journal of Interdisciplinary Studies in Education, 2024)
This study aims to explore Hawassa University academics staffs’ understanding, practice and institutional challenges pertaining to their CPD engagement. To this end, we employ exploratory case study as research design involving interview, FGD and document analysis as sources of data. The data were analyzed using thematic descriptive narration based on themes created by the basic questions of the study. The findings reveal that at Hawassa University, academic staffs understood CPD in different ways and practiced both formally and informally. The major challenges that hinder practical effectiveness of CPD includes: misunderstanding of its importance, lessened motivation of academics staffs to participate, inability of the institution to make the content of CPD relevant to academics’ current needs and insufficient financial provisions. Finally, we argue that as an inevitable prerequisite for the competitiveness of the individuals and their respective institutions, CPD of academics should be undertaken using innovative and needs systematized approach.